Calibrating canines—a universal detector calibrant for detection dogs - Maughan, Michele N.; Gadberry, Jenna D.; Sharpes, Caitlin E.; Buckley, Patricia E.; Miklos, Aleksandr E.; Furton, Kenneth G.; DeGreeff, Lauryn E.; Hall, Nathaniel J.; Greubel, Robin R.; Sloan, Katylynn B. (Frontiers in Allergy, 2024)
Since the advent of the Universal Detector Calibrant (UDC) by scientists at Florida International University in 2013, this tool has gone largely unrecognized and under-utilized by canine scent detection practitioners. The UDC is a chemical that enables reliability testing of biological and instrumental detectors. Training a biological detector, such as a scent detection canine, to respond to a safe, non-target, and uncommon compound has significant advantages. For example, if used prior to a search, the UDC provides the handler with the ability to confirm the detection dog is ready to work without placing target odor on site (i.e., a positive control), thereby increasing handler confidence in their canine and providing documentation of credibility that can withstand legal scrutiny. This review describes the UDC, summarizes its role in canine detection science, and addresses applications for UDC within scent detection canine development, training, and testing.